Equilibrium Warrant Pricing Models and Accounting for Executive Stock Options - Noreen, Eric; Wolfson, Mark (Journal of Accounting Research, 1981)
Executive compensation, Executive stock options, Equilibrium warrant pricing model, APB opinion No. 25